Research on the Application of Digital Twin Technology in Equipment Maintenance - Shi, Junbin; Shan, Yan; Han, Hongmin (International Journal of Computer Science and Information Technology, 2024)
Digital twin technology is to make full use of the data such as physical model, sensor update, running history, integrate the multi-subject multi-physical quantity, multi-scale, multi-probability simulation process, complete the mapping in virtual space, thus reflect the whole life cycle process of the corresponding entity equipment. In this paper, the digital twin of a certain type of equipment system is studied to realize the operation condition monitoring, fault intelligent diagnosis and so on, so as to improve the maintenance efficiency and effect of the equipment.